(untitled) (ModaPalavra e-periódico, 2022)
In the economic and business context in which we live, characterized by several changes and advances, mainly in consumption, we can see that creative and purposeful businesses and entrepreneurs have been consolidated. Fashion is one of the markets that has shown such changes evidenced by some brands that are concerned with issues of sustainability and purpose. The main objective of this article is to identify the applicability and uses of the concepts of entrepreneurship, fashion and purpose, based on a case study of the Somos Numa brand. The methodology used is descriptive, with the case study of the brand. The data were collected through in-depth interviews with the owners and documentary analysis.